Autistic Spectrum Disorder and Savant Syndrome: A real paradox between cognitive deficit and genius (Research, Society and Development, 2021)
Introduction: The Autistic Spectrum Disorder (ASD) is expressed in childhood, its characteristic being a delay in the individual's development, anomalous social interactions, and an intellectual disability may still be present. This disorder may include Savant Syndrome, characterized by remarkable talent in one or more domains, such as memory, music, art, mathematics. Objective: To address the relationship between ASD and Savant Syndrome, a rare situation in which a person with intellectual deficit has a great degree of genius and wisdom, having many abilities through his extraordinary memory. Methodology: This is a descriptive research of the integrative literature review type, which seeks evidence on the relationship between ASD and Savant Syndrome. The search was performed using PubMed, MEDLINE, Scielo, CDSR, Google Scholar, BVS and EBSCO databases, from 2000 to 2021. Thus, 21 scientific productions were totaled for the integrative literature review. Results: There is no consensus on exactly how wise skills are used in ASD patients. Some studies show that savants have no difference in standard intelligence compared to other individuals with ASD. Therefore, it may be that your skills develop simply through many hours of prolonged practice. Conclusion: The skills "savants" themselves may not be as relevant, given that the behavior is performed repetitively. It is important to explore further how these factors can influence how different skills can be an important next step in understanding wise skills.